2016
DOI: 10.3945/ajcn.115.127944
|View full text |Cite
|
Sign up to set email alerts
|

Trends in racial/ethnic and income disparities in foods and beverages consumed and purchased from stores among US households with children, 2000–2013,

Abstract: Background: It is unclear whether racial/ethnic and income differences in foods and beverages obtained from stores contribute to disparities in caloric intake over time. Objective: We sought to determine whether there are disparities in calories obtained from store-bought consumer packaged goods (CPGs), whether brands (name brands compared with private labels) matter, and if disparities have changed over time. Design: We used NHANES individual dietary intake data among households with children along with the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Likewise, the households with the lowest incomes (,185% FPL) obtained significantly more added sugars in both absolute and relative terms than did households with incomes $400% FPL. These findings are consistent with earlier research that found calories from store-obtained beverages decreased in all subpopulations, but reductions in calories from packaged beverages purchased in 2009-2012 were slower in black and low-income households than in white and highincome households (28). Nonetheless, earlier work on packaged beverages has only been able to consider calories or total sugars, not added sugars specifically.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, the households with the lowest incomes (,185% FPL) obtained significantly more added sugars in both absolute and relative terms than did households with incomes $400% FPL. These findings are consistent with earlier research that found calories from store-obtained beverages decreased in all subpopulations, but reductions in calories from packaged beverages purchased in 2009-2012 were slower in black and low-income households than in white and highincome households (28). Nonetheless, earlier work on packaged beverages has only been able to consider calories or total sugars, not added sugars specifically.…”
Section: Discussionsupporting
confidence: 89%
“…Thirty-four studies were included in this scoping review [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Information on customer purchasing assessment methodologies used across studies is shown in ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies (44.1%) examined purchasing outcomes across racial and/or ethnic groups [ 27 , 29 , 30 , 39 , 42 , 43 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 53 , 54 ]. All studies examined purchasing among NHW, 14 examined purchasing among NHB, 14 studied purchasing among Hispanic, nine examined purchasing among non-Hispanic Other (or a different author definition that collapsed multiple racial/ethnic groups), and three investigated purchasing among Asian (using the author definition).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations